OsHIPP17 is involved in regulating the tolerance of rice to copper stress - Shi, Yang; Jiang, Nan; Wang, Mengting; Du, Zhiye; Chen, Ji; Huang, Yanyan; Li, Mingyu; Jin, Yufan; Li, Jiahao; Wan, Jian; Jin, Xiaowan; Zhang, Lang; et al. (Frontiers in Plant Science, 2023)
Heavy metal-associated isoprenylated plant proteins (HIPPs) are proteins play vital roles in metal absorption, transport and accumulation. But, so far, only several plant HIPPs have been functionally analyzed. In this study, a novel HIPP member OsHIPP17 was functionally characterized, which was involved in the tolerance to copper (Cu). OsHIPP17 proteins were targeted to the nucleus. The Cu concentration reached 0.45 mg/g dry weight due to the overexpression of OsHIPP17 in yeast cells. Meanwhile, the overexpression of OsHIPP17 resulted in the compromised growth of Arabidopsis thaliana under Cu stress. The root length of Oshipp17 mutant lines was also significantly reduced by 16.74-24.36% under 25 μmol/L Cu stress. The roots of Oshipp17 rice mutant showed increased Cu concentration by 7.25%-23.32%. Antioxidant enzyme activity was also reduced in rice due to the knockout of OsHIPP17. Moreover, the expression levels of cytokinin-related genes in plants under Cu stress were also affected by overexpression or knockout of OsHIPP17. These results implied that OsHIPP17 might play a role in plant Cu toxic response by affecting cytokinin homeostasis. Simultaneously, our work may shed light on the underlying mechanism of how heavy metals affect the plant growth and provide a novel rice genetic source for phytoremediation of heavy metal-contaminated soil.